Transcendental Communication in MH Saifurrahmi's Nerve Reflex Therapy: An Epistemological Perspective of Irfani - Gusli bambang irawan (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2023)
Transcendental communication is a relatively new concept in the realm of communication studies. It refers to communication between a servant and God, characterized as transcendent or vertical. One instance of this is observed in the phenomenon of nerve reflex therapy by MH Saifurrahmi, where transcendental communication is utilized. Transcendental communication is also a recent development in the field of communication studies. This article examines the transcendental communication phenomenon present in MH Saifurrahmi's nerve reflex therapy in Mayang, Jambi City. The research adopts a qualitative descriptive approach, collecting data through observations, interviews, and documentation. The research findings reveal that in the nerve reflex therapy conducted by MH Saifurrahmi in Mayang, Jambi City, the phenomenon involves the use of "tawasul" (mediation) as a means of transcendental communication directed toward his mentors and elders, ultimately reaching out to Allah. Additionally, prayer gatherings ("sholat hajat") and supplications serve as measures for healing, advised by MH Saifurrahmi before administering nerve reflex therapy. The outcome of this mediation manifests as intuitive insights experienced by MH Saifurrahmi, enabling him to diagnose conditions and recommend herbal remedies tailored for treatment.